Bioinspired design and optimization for thin film wearable and building cooling systems. (16th December 2021) - Grinham, Jonathan; Hancock, Matthew J; Kumar, Kitty; Bechthold, Martin; Ingber, Donald E; Aizenberg, Joanna
Abstract: In this work, we report a paradigmatic shift in bioinspired microchannel heat exchanger design toward its integration into thin film wearable devices, thermally active surfaces in buildings, photovoltaic devices, and other thermoregulating devices whose typical cooling fluxes are below 1 kW m −2 . The transparent thermoregulation device is fabricated by bonding a thin corrugated elastomeric film to the surface of a substrate to form a microchannel water-circuit with bioinspired unit cell geometry. Inspired by the dynamic scaling of flow systems in nature, we introduce empirically derived sizing rules and a novel numerical optimization method to maximize the thermoregulation performance of the microchannel network by enhancing the uniformity of flow distribution. The optimized network design results in a 25% to 37% increase in the heat flux compared to non-optimized designs. The study demonstrates the versatility of the presented design and architecture by fabricating and testing a scaled-up numerically optimized heat exchanger device for building-scale and wearable applications.